Aulas de cirurgia no centro da América do Sul (1808-16) Surgical classes in the middle of South America (1808-16) - Nauk Maria de Jesus (História, Ciências, Saúde: Manguinhos, 2004)
O presente artigo tem como objetivo analisar as propostas de aulas de cirurgia na capitania de Mato Grosso, ampliando as reflexões sobre a arte de curar no período colonial. As propostas dessas aulas estão inseridas em um conjunto de medidas tomadas no período e refletem a preocupação das autoridades com a saúde do bem comum. As a contribution to reflections on the art of curing during the colonial period, the article analyzes the proposal to hold surgical classes in the captaincy of Mato Grosso. This proposal was part of a set of measures taken during the period, measures that reflected the government authorities' concern with the public health.